The Development of Student Worksheet in Colligative Properties of Solution to Train Creative Thinking Skills (Universitas Negeri Surabaya, 2020)
The study aims to produce student worksheet in colligative properties of solution that are valid, practical, and effective. The method of student worksheet development uses R&D method but only reached the limited trial of development stage. The developed student worksheet were tested on limited trial to twelve 12th grade students who had recieved colligative properties of solution material. Based on the results of the research, the percentage of validity in content criteria is 80.22%, language criteria is 80.67%, presentation criteria is 80.00%, and graphics criteria is 83,33%. The percentage of practicality in content criteria is 93.33%, language criteria is 91.67%, presentation criteria is 91.67%, and graphics criteria is 97.92%.The effectiveness of student worksheet based on knowledge has an average score of 85 and based on creative thinking skills, it has average percentage of characteristic of creative thinking on fluency is 82.64%, flexibility is 84.45%, elaboration is 88.89%, and originality is 90.28%. Thus the results of this research indicate that the developed student worksheet is valid, practical, and effective. Keywords: Student worksheet, creative thinking, validity, practicality, effectiveness